Complete chloroplast genome sequences of Lilium: insights into evolutionary dynamics and phylogenetic analyses - Yun-peng Du (Nature Portfolio, 2017)
Abstract Lilium is a large genus that includes approximately 110 species distributed throughout cold and temperate regions of the Northern Hemisphere. The species-level phylogeny of Lilium remains unclear; previous studies have found universal markers but insufficient phylogenetic signals. In this study, we present the use of complete chloroplast genomes to explore the phylogeny of this genus. We sequenced nine Lilium chloroplast genomes and retrieved seven published chloroplast genomes for comparative and phylogenetic analyses. The genomes ranged from 151,655 bp to 153,235 bp in length and had a typical quadripartite structure with a conserved genome arrangement and moderate divergence. A comparison of sixteen Lilium chloroplast genomes revealed ten mutation hotspots. Single nucleotide polymorphisms (SNPs) for any two Lilium chloroplast genomes ranged from 8 to 1,178 and provided robust data for phylogeny. Except for some of the shortest internodes, phylogenetic relationships of the Lilium species inferred from the chloroplast genome obtained high support, indicating that chloroplast genome data will be useful to help resolve the deeper branches of phylogeny.